FAKTOR YANG MEMPENGARUHI PEMILIHAN JURUSAN OLEH PESERTA DIDIK DI SMA NEGERI 1 SOLOK - Pratama, Puji Yani; Hasan, Marwisni; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
Based of phenomenon which researcherÂ found out in the field, the researcher considered that was found students whose majors were not suitable with their psychology. Therefore, the researcher took it as a case to study: How internal and external factorsÂ influenced students when they chose their majors in SMA Negeri 1 Solok. This research wanted to deseribe: the factors which influenced students when they chose their majors in SMA Negeri 1 Solok. This research was decripsive research with population werw 333 students. Sample of this research was purposive random sampling. The data of this research were pimer and secunder. Instrument that used in collecting the data was questionaire and it technique was percentage formula.With refesence to finding of the research, so students talent factor in choosing that was enough criteria, interest was enough, intelligence was good, motivation was good, ability was enough, care was good and dream was good. Nevertheles, students family factor in choosing that was good criteria, scool was enough, facility was enough and society was good. This means that students who chose their majors related to external factor was good.